From Environmental Epigenetics to the Inheritance of Acquired Traits: A Historian and Molecular Perspective on an Unnecessary Lamarckian Explanation - Mauro Mandrioli (Biomolecules, 2023)
In the last decade, it has been suggested that epigenetics may enhance the adaptive possibilities of animals and plants to novel environments and/or habitats and that such epigenetic changes may be inherited from parents to offspring, favoring their adaptation. As a consequence, several Authors called for a shift in the Darwinian paradigm, asking for a neo-Lamarckian view of evolution. Regardless of what will be discovered about the mechanisms of rapid adaptation to environmental changes, the description of epigenetic inheritance as a Lamarckian process is incorrect from a historical point of view and useless at a scientific level. At the same time, even if some examples support the presence of adaptation without the involvement of changes in DNA sequences, in the current scenario no revolution is actually occurring, so we are simply working on a stimulating research program that needs to be developed but that is, at present, completely Darwinian.